2014
DOI: 10.1002/oby.20791
|View full text |Cite
|
Sign up to set email alerts
|

Rapid gastric and intestinal transit is a major determinant of changes in blood glucose, intestinal hormones, glucose absorption and postprandial symptoms after gastric bypass

Abstract: Objective: To evaluate the effect of modulating pouch emptying (PE) and SI transit of glucose after Roux-en-Y gastric bypass (RYGB) on blood glucose, incretin hormones, glucose absorption and gastrointestinal (GI) symptoms. Methods: Ten RYGB patients were studied twice in random order, receiving either a 150 ml glucose drink (200 kcal) or the same solution infused into the proximal Roux-limb at 4 kcal/min. Data were compared with 10 healthy volunteers who received a 4 kcal/min duodenal infusion. PE, cecal arri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 39 publications
4
89
0
Order By: Relevance
“…Scintigraphic studies after RYGB have shown detectable amounts of solid food in the small intestine 15 min after meal start but could not distinguish between the alimentary and common limb (3). Transit of liquids may be even faster as suggested by reports of cecal arriving time of 26 min after ingestion of a glucose drink (21) and maximal concentrations of paracetamol almost immediately after intake (4). Consistent findings of exaggerated secretion of L-cell products after RYGB (22) also support a rapid passage of nutrients to distal segments of the small intestine where L cells are located with the highest density (23).…”
Section: Discussionmentioning
confidence: 99%
“…Scintigraphic studies after RYGB have shown detectable amounts of solid food in the small intestine 15 min after meal start but could not distinguish between the alimentary and common limb (3). Transit of liquids may be even faster as suggested by reports of cecal arriving time of 26 min after ingestion of a glucose drink (21) and maximal concentrations of paracetamol almost immediately after intake (4). Consistent findings of exaggerated secretion of L-cell products after RYGB (22) also support a rapid passage of nutrients to distal segments of the small intestine where L cells are located with the highest density (23).…”
Section: Discussionmentioning
confidence: 99%
“…If so, we would predict that compensations such as changes in the secretion of prandial hormones will occur in discreet regions of the gut that are most affected by surgery, i.e., regions of the gut that face the greatest increase in metabolic demand, as opposed to homogenous changes throughout the gut. Indeed, when Nguyen et al infused nutrients directly into the bypassed segment of RYGB patients, a region in which the metabolic demands of the tissue actually decrease, prandial GLP-1 responses appeared normal relative to those of control subjects (Nguyen et al, 2014). The same patients, however, showed robust increases in prandial GLP-1 when nutrients were presented to the common limb via the stomach.…”
Section: The Role Of Enteroplasticity In the Mechanisms Underlying Bamentioning
confidence: 99%
“…As opposed to solids, liquids were shown to empty faster into the cecum. The faster liquid transit may contribute to the early rise in PYY and GLP-1 after RYGB and potentially improve satiety [85]. In summary, after RYGB, liquids small intestinal transit seems to be faster while the opposite holds for solids.…”
Section: Intestinal Motility After Rygbmentioning
confidence: 93%
“…With accelerated emptying, gastric retention is decreased after RYGB [79][80][81][82][83][84][85]. In a recent study, using Scintigraphy and 3DCT, accelerated gastric emptying was found to correlate with small volume of gastric pouch and lower risk of weight regain after RYGB [86].…”
Section: Gastric Function After Rygb and Impact On Weight Lossmentioning
confidence: 97%
See 1 more Smart Citation